Pneumonia in domestic rabbits in Egypt. Strain types and methods of control - Gergis S.M. (Rabbit production in hot climates, 1994)
Out of 119 rabbit carcases with pneumonica examined bacteriologically, 7 bacterial species could be isolated as causative agents of single infection. Pasteurella multocida was isolated among other bacterial species in 27.7 per cent of pneumonic lungs. Seventy isolates of P. multocida were serotyped. Capouler typing revealed that 93 per cent were type A and 7 per cent belonged to type D. Somatic typing revealed the presence of seven O groups. Combination of both typing systems revealed that A:3, A:12 and D:11 were the most frequent isolates. A polyvalent adfuvinated vaccine prepared from these isolates affored protection in vaccinated rabbits against septicaemic pasteurellosis.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)